Reconstruction of Minor Criminal Case Settlement By The Prosecutor's Office Through Restorative Justice - Syahroni, Teuku; Yusuf Hasibuan, Fauzie; Kristiawanto , Kristiawanto (Pelopor Publikasi Akademika, 2025)
This study analyzes the implementation of restorative justice in handling minor crimes by the Prosecutor's Office and offers a policy reconstruction to enhance its effectiveness and achieve substantive justice within the criminal law system. Employing a normative juridical method, the research utilizes legislative, case, historical, comparative, and conceptual approaches. The analysis draws on theories of justice by John Rawls, Lawrence M. Friedman’s theory of the legal system, and Howard J. Zehr’s theory of restorative justice. The findings reveal that restorative justice is not yet optimally implemented due to disparities in regional policy execution, weak legal infrastructure, and a prevailing retributive mindset among officials and the public. As a solution, the study recommends the mandatory implementation of restorative justice for minor crimes meeting specific criteria, clarifying application standards, enhancing law enforcement training, establishing more restorative justice centers, and strengthening supervision and evaluation mechanisms. The novelty of this research lies in identifying multidimensional barriers, integrating a comprehensive theoretical framework, and proposing a more systematic policy reconstruction. With improved implementation, restorative justice can become a primary tool in resolving minor offenses, reducing overcrowding in correctional facilities, and fostering a more equitable, recovery-focused legal system.